2017
DOI: 10.1038/ncomms15919
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the thermal conductivity along an individual silicon nanowire by selective helium ion irradiation

Abstract: The ability to engineer the thermal conductivity of materials allows us to control the flow of heat and derive novel functionalities such as thermal rectification, thermal switching and thermal cloaking. While this could be achieved by making use of composites and metamaterials at bulk length-scales, engineering the thermal conductivity at micro- and nano-scale dimensions is considerably more challenging. In this work, we show that the local thermal conductivity along a single Si nanowire can be tuned to a des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 55 publications
(70 reference statements)
3
53
0
Order By: Relevance
“…An electron‐beam technique was employed to measure the thermal conductivity of single nanowires . Briefly, we use the focused electron beam as a heating source and the two suspended islands with platinum loops act as resistance thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…An electron‐beam technique was employed to measure the thermal conductivity of single nanowires . Briefly, we use the focused electron beam as a heating source and the two suspended islands with platinum loops act as resistance thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…creation of amorphous segments along silicon nanowire. We had previously demonstrated the creation of an amorphous region of desired length along a single-crystal silicon nanowire by helium ion irradiation 27 . To obtain an amorphous silicon region with a much cleaner and sharper interface, we modified the irradiation conditions by calibrating the doses before irradiating the target nanowires, with details described in Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Semiconductor NWs have attracted considerable attention due to their potential applications in many areas, such as electronic devices [117,118], biosensors [119,120], thermoelectric devices [121][122][123][124] and optoelectronic devices [125][126][127][128]. The interest of investigating phonon transport in SiNWs has been greatly stimulated [129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145] since experiments [12,29] revealed that an approximately 100-fold reduction in thermal conductivity over bulk Si can be achieved in SiNWs, while the electrical conductivity and electron contribution to Seebeck coefficient are still similar to those of bulk silicon, which indicated that SiNWs could be applied as high-performance nanoscale thermoelectric materials. Further reducing thermal conductivity of SiNWs is critically important for achieving higher thermoelectric performance.…”
Section: Coherent Phonon Transport In Nwsmentioning
confidence: 99%